Clinical Patterns and Outcome of Acute Poisoning Cases at a Tertiary Care Hospital in Eastern Nepal - Mandal, Madan Krishna; Mandal, Namita Kumari; Shah, Rohit Kumar (Journal of Nobel Medical College, 2025)
Background: Acute Poisoning is a major health problem with significant morbidity and mortality affecting people of all age groups. The objective of the present study was to find out the clinical features, epidemiological profile, pre-hospital treatment practice and the role of triage variables as severity and outcome indicators. Materials and Methods: All emergency patients with acute oral poisoning were included. Data on triage, demographics, clinical features, poison characteristics, and pre-hospital treatment were recorded using a semi-standardized Proforma. Primary outcomes were mortality and survival; secondary outcomes included admission details and complications. Results: Adult poisoning comprised 3.3% of Emergency admissions, mainly affecting young adults (21–30 years, 33.4%) with a female predominance (62.9%). Most were married (67.6%), educated up to secondary level (62.4%), and were housewives (42.5%) or students (30.3%) from nearby districts. Intentional suicides (92.2%), primarily with organophosphates (30.3%) and rat killers (20.1%), predominated. Over 59.7% arrived within 4 hours, mostly at night (69.6%). Gastrointestinal symptoms (81.1%) were common, with Glasgow Coma Scale of 13–15 in 80.8%. Antidotes were given in 31.6%, intubation in 9%, and complications in 17.5%. Mortality was 6.3%, while 78.4% survived; fatalities had lower Blood Pressure, oxygen saturation, and consciousness. Conclusion: Poisoning is common with agricultural products with housewives and students forming the majority. Young age is commonly involved. Suicidal act at home presenting with gastro- intestinal symptoms visiting at night is common.